2023
DOI: 10.1037/stl0000221
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness misconceptions among undergraduates: Prevalence, correlates, and instructional implications.

Abstract: Although several published studies have examined students' misconceptions about psychology in general, only 1 study has focused exclusively on misconceptions about mental illness, and that study examined only 5 such misconceptions. To overcome this gap in our knowledge and to devise effective teaching strategies to disabuse college students of false information, an up-to-date survey of current misconceptions and their correlates among students is necessary. In this study, 375 undergraduates enrolled in introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…Students may have disregarded these beliefs based on information learned in other psychology courses. Thus, myths held by students entering abnormal psychology may be different from students in introductory psychology courses, as discussed by Basterfield and colleagues (2020). Additionally, students at the onset of class indicated that the most influential sources of information about abnormal psychology came from instructors, internet, and movies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students may have disregarded these beliefs based on information learned in other psychology courses. Thus, myths held by students entering abnormal psychology may be different from students in introductory psychology courses, as discussed by Basterfield and colleagues (2020). Additionally, students at the onset of class indicated that the most influential sources of information about abnormal psychology came from instructors, internet, and movies.…”
Section: Discussionmentioning
confidence: 99%
“…Students who created a myth-debunking poster within their course discussion forum demonstrated significantly greater accuracy of psychological knowledge (LaCaille et al, 2019). More recently, researchers constructed a 105-item questionnaire, the Abnormal Psychology Misconception Questionnaire (APMQ) to examine prevalence of mental health myths endorsed by students in introductory psychology courses (Basterfield et al, 2020). The researchers found a range of myth endorsement, from 3% to 96% of participants endorsing myth items across both versions of the APMQ (Basterfield et al, 2020).…”
mentioning
confidence: 99%
“…The dichotomous response format (true/false) has been, for many years, the chosen by researchers ( Basterfield et al, 2020 ; Brown, 1983 ; Ferrero, Garaizar & Vadillo, 2016 ; Furnham, Callahan & Rawles, 2003 ; Gardner & Dalsing, 1986 ; Hughes, Lyddy & Lambe, 2013 ; Kowalski & Taylor, 2004 ; Lamal, 1995 ; Taylor & Kowalski, 2004 ; Taylor & Kowalski, 2012 ; Torres, Boccacini & Miller, 2006 ; Vaughan, 1977 ). This format is associated with a series of limitations ( Bensley & Lilienfeld, 2017 ; Griggs & Ransdell, 1987 ; Hughes, Lyddy & Lambe, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive research on myths in Psychology in other countries—see, for example, Russia ( Aleksandrova-Howell et al, 2020 ), North America ( Basterfield et al, 2020 ; Bensley & Lilienfeld, 2017 ; Brown, 1983 ; Gardner & Brown, 2013 ), United Kingdom ( Furnham, Callahan & Rawles, 2003 ; Furnham & Hughes, 2014 ; Furnham & Grover, 2019 ), or India ( Kishore et al, 2011 )—a study of the same characteristics has not yet been carried out in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike specialists, the general public simply may not know whether it is more or less plausible that a particular manipulation or treatment will have an effect. Widespread misconceptions about many psychological topics are well-documented ( Lilienfeld et al, 2011 ), including misconceptions about mental illness and its treatment ( Basterfield et al, 2020 ). Also, research findings that confirm our beliefs may be more readily accepted, while unexpected findings are met with doubt ( e.g.…”
Section: Introductionmentioning
confidence: 99%